EXPLORING SUSTAINABLE DIGITAL MARKETING PRACTICES OF YOUTH ENTREPRENEURS: A QUALITATIVE CASE STUDY - Nazri, Farahana Mohd; Shuib, Fatin Husna; Suki, Amirah Ahmad; Haque, A. K. M. Ahasanul (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This case study explores at how young entrepreneurs may use sustainable digital marketing and how it can help them run their businesses on a daily basis and stay in business for a long time. In a corporate world that is becoming more digital and where online competition is getting tougher, young entrepreneurs need to constantly find a balance between making smart business decisions that are good for the environment and using marketing methods that work. This research employs a qualitative case study methodology, including data collecting through semi-structured interviews and document analysis of youth entrepreneurs across diverse business sectors. The study's findings indicate that sustainability elements are integrated into digital marketing efforts via ethical online communication, responsible content creation, customer engagement centered on consumer needs, and the strategic utilization of digital platforms to manage expenses and mitigate environmental effects. These practices help make the brand more trustworthy, improve relationships with customers, and make the firm more resilient. This survey also finds some important problems, such as not having enough resources, not having enough digital skills, and being under pressure to put short-term sales targets ahead of long-term sustainability goals. This study shows that sustainable digital marketing is a useful and doable way for managers to help young entrepreneurs' businesses do better and be more competitive. The results of this study provide valuable insights for youth entrepreneurs, entrepreneurship support organizations, and governments in their initiatives to enhance sustainability-oriented digital marketing practices within the entrepreneurial ecosystem.